Kepercayaan kenan dalam masyarakat Melayu: Kajian dari perspektif hukum Islam - Mohd Anuar, R.; Syamsul Azizul, M. (2014)

(untitled)
Every society has its own beliefs and taboos which control their members implicitly. Taboo is an oral tradition practiced mostly in Malay traditional society. In Malay society, there are several taboos. One of those taboos is kenan, which is closely related to pregnant women taboos. Basically, kenan is part of the process of cause and consequence, which is considered as incidental to whether an illness or disability suffered by a newborn baby is due to taboo violation by a parent when the baby was still in the mother's womb. The origin of kenan was derived from society's intention to preserve the relationship between man and nature, but eventually this intention has been misunderstood by later generations with lateral interpretations until it was known as taboos as well as superstitions among Malay-Muslims. This study attempts to scrutinize the concept of kenan and related discussions fro,m the Islamic perspective and also medical views on that subject. The findings show that this taboo is regarded as syirk. Consequently this belief is prohibited for Malay- Muslim to practice in their daily life.